The impact of possible-offer announcements on the wealth effect of target firms. Issue 15 (13th October 2019) - Li, Hang; Zhou, Dan
ABSTRACT: The stock market materially and positively responds to released information on possible offers, likely because such announcements signal the high probability that formal bids will be offered. If potential takeover discussions are revealed earlier, then target shareholders will gain significantly lower abnormal returns around the time of when formal offers are announced. Financial bidders are less likely to approach targets with earlier possible offers; however, if they do offer possible takeovers, they need to pay incrementally higher bid premiums in their formal offers. The reform inherent in the U.K. Takeover Code of 2011 weakens a bidder's willingness to offer possible takeovers. The pre-reform effects of possible offers on the wealth effect of targets differ from those seen after the reform.